Effects of ground coal bottom Ash on the properties of concrete - Mangi, Sajjad Ali; Wan Ibrahim, M. H.; Jamaluddin, N.; Arshad, M. F.; Putra Jaya, Ramadhansyah (Taylor's University, 2019)
Coal bottom ash is a waste material produced by the coal based thermal power plants. The annual production of coal bottom ash(CBA)in India is 25 million tons, in US 14 million tons, Europe 4 million tons and in Malaysia about 1.7 million tons, which creates environmental problems for the global society. Hence, the aim of this study is to utilize CBA in concrete as a partial cementer placement. In this study, the CBA was ground for three different grinding periods 20, 30 and 40 hours and concrete mix was prepared at a replacement rate of 10, 20 and 30% by weight of cement. Total 120 specimens were cast to assess the fresh and hardened properties of concrete at the age of 28days. For the fresh mix concrete, workability reduced as quantity of ground CBA increased in the mix. However, the density of concrete was continuously declined due to addition of ground CBA and opposite behaviour was observed in water absorption capacity. The high rate of water absorption was observed as the fineness and replacement level increased in the mix. Furthermore, no significant rise in the compressive and flexural strength was recorded in this study but with 10% ground CBA as a replacement of ordinary cement the targeted compressive strength of concrete was achieved. Besides that, the splitting tensile strength was increased about8% in concrete containing 10% ground CBA (obtained through 30 hours grinding period)as compared with the control specimen. Hence, it was concluded that the ground CBA has a good potential to be utilized as cement replacement in concrete which will reduce the construction cost and minimize the environmental burden.